"Carefully and Cautiously": How Canadian Cultural Memory Workers Review Digital Materials for Private and Sensitive Information - Whyte, Jess; Walsh, Tessa (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
This exploratory study is based on semi-structured interviews with digital preservationists working in Canada. The goal was to understand how participants are reviewing sensitive personal information in their digital materials and identify the challenges they face in this work. Findings include a summary of current practices in place (e.g., risk profiling, using software tools for triage, and consultation with donors and/or community), and a list of challenges (e.g., IT or systems infrastructure, scale, barriers to access for software tools, and funding restrictions). The implications of these findings are that Canadian memory workers require time, staff, support, and training, while developers of assistive-software tools for this work should address tool limitations and prioritize user-friendly interfaces. Grant funding stipulations should also be revised to allow for diverse access options, while investment in controlled access repositories would enable responsible online access to complex collections.